INTEGRASI SISTEM PENDIDIKAN PADA LEMBAGA FORMAL DAN LEMBAGA NONFORMAL - Iwan Sopwandin; Munawar, Siti Hapsoh, Sumarna, Cecep Palahudin, Siti Nurjalilah (CV. ADIBA AISHA AMIRA, 2024)
Integration in the meaning of the relationship between formal and non-formal education is the existence of a unity of purpose and an educational system that is mutually beneficial between the two. This research aims to analyze the integration between formal and non-formal education, in this case schools and Islamic boarding schools under the auspices of the Miftahul Ulum Gunungbubut Sodonghilir Tasikmalaya Islamic Education Foundation. The research method used is qualitative with a descriptive analysis approach. Data collection techniques include observation, interviews and documentation studies. Meanwhile, the interactive model which includes data condensation, data presentation and conclusions is used as a data analysis tool. The results of this research show that several things are integrated between schools and Islamic boarding schools, namely related to: 1) discounts on school entrance fees for students who live in Islamic boarding schools; 2) lesson schedule, and 3) holiday schedule.